Rekayasa Ulang Proses Bisnis (Business Process Enggineering) Untuk Mencapai Simplipliflying The Airliness Business - M. N. Nasution (Research and Development Agency of The Ministry of Transportation, 2010)
Business process reengineering (BPR) is one of the efforts to increase sumpriority compatative incisive. With BPR will simplified process of service passangers without decrease of comfortable and safety passangers, until opeation cost can push down low.In airlines business this moment expand/develop simplifying the airliness business with to make use of electronic technology in passengers services, until can low cost in as much as great as possible and give passenger simplifying in use of air transport.